Pengaruh Tipe Kepribadian dan Lingkungan Pergaulan terhadap Perilaku Seksual Remaja di SMP "XY" Swasta Kota Malang - Nur Aini (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
Adolescent is a period of transition, emotionally unstable so that they are easily violated the norms in society. Two major problems that are often experienced by adolescents is an abuse of psychotropic drugs and sexual behavior. Adolescent sexual behavior nowadays leads to deviant behavior. The purpose of this research was to know the effectiveness of the personality type and associating environment toward adolescent sexual behavior. Method: Observational study with cross sectional design. The population was student at class VII and VIII totaled 174, the sample was 121 students taken by proportionate stratified random sampling. The independent variable was personality type and associating environment, dependent variable was sexual behavior. The data collected by questionnaire and analyzed by multiple regression logistic. Result: The personality type most were introvert and extrovert as 54 adolescents (44,6%); good associating environment was 79 adolescents (65,2%); and negative sexual behavior as 70 adolescents (57,9%), with most types were holding hands when dating and kissing. Based on the regression equation, obtained factor personality type could increase the value of 0,753 sexual behavior while associating environment 1,772 and p value (0,000) <  (0,05). Discussion:Personality type and social environment together has an effect to the sexual behavior. Adolescent with extrovert personality had a more positive attitude toward sexual behavior than introvert adolescent. Because they were adaptable, open and are likely to share problems with others, so introvert adolescent risk in doing free sex. However, the environment and personality are also interrelated, because the associating environment could shape the personality.